Improving depth sensitive fluorescence spectroscopy with wavefront shaping by spectral and spatial filtering - Hsieh, Chao-Mao (2021)
Depth sensitive optical spectroscopy preferentially detects optical spectra from different depths in layered samples, which plays a crucial role in many applications such as the optical diagnosis of epithelial precancer and cancer. In depth sensitive optical measurements, multiple light scattering in tissues significantly degrades the depth sensitivity to a subsurface target layer. To address this issue, feedback based wavefront shaping led by guide stars can be used to refocus light to increase the depth sensitivity to a target layer. However, the lack of intrinsic guide stars in tissues or tissue-like samples often leads to poor enhancement in depth sensitive Raman/fluorescence measurements (20% in the past literature) from the target layer due to the contribution from the overlaying non-target layer. In this study, we demonstrate that spatial filtering and spectral filtering can significantly improve the performance of depth sensitive fluorescence spectroscopy assisted by feedback based wavefront shaping in tissue-like scattering phantoms. The two filtering techniques work by effectively increasing the relative contribution from the target layer to the feedback signal during wavefront optimization through spatially and spectrally rejecting off-target fluorescence light, which is essentially similar to the role of time or coherence gating. When the filtering techniques are applied, a maximum of three-fold enhancement in fluorescence contribution from the target layer is observed, which is in contrast to nearly no enhancement in case of no filtering. This significant enhancement has not been reported previously for depth sensitive optical spectroscopy in the area of feedback based wavefront shaping. Therefore, our work represents a new advance towards the application of wavefront shaping in depth resolved optical spectroscopy for the characterization of layered structures such as epithelial tissues or drug tablets, in which the creation of an external guide star is challenging or not allowed.